Short-form measures of diabetes-related emotional distress: The Problem Areas in Diabetes Scale (PAID)-5 and PAID-1 - McGuire, B.E. (2010)
Aims/hypothesis: We wanted to identify a five-item short form of the Problem Areas in Diabetes Scale and a single-item measure for rapid screening of diabetes-related emotional distress. Methods: Using an existing database of 1,153 patients with diabetes, we conducted a principal-components analysis to identify a set of five items and then conducted a reliability analysis and validity checks. From those five items, we identified the item with the strongest psychometric properties as a one-item screening tool. Results: We identified a reliable and valid short version of the Problem Areas in Diabetes Scale (PAID) comprising five of the emotional-distress questions of the full PAID items (PAID-5, with items 3, 6, 12, 16, 19). The PAID-5 has satisfactory sensitivity (94%) and specificity (89%) for recognition of diabetes-related emotional distress. We also identified a one-item screening tool, the PAID-1 (Question 12: Worrying about the future and the possibility of serious complications), which has concurrent sensitivity and specificity of about 80% for the recognition of diabetes-related emotional distress. Conclusions/ interpretation: The PAID-5 and PAID-1 appear to be psychometrically robust short-form measures of diabetes-related emotional distress.